Ethyl Methane Sulphonate - A Potent Mutagen For Inducing Genetic Variability In Saffron (Crocus Sativus L.) (Applied Biological Research, 2017)
Mutagenic effects of three concentrations of ethyl methane sulphonate [EMS] (0.1, 0.15 and 0.20%) to improve floral, foliar, corm and quality attributes in  saffron was evaluated. A considerable genetic variability was observed among  the mutagenic lines created with 0.15 and 0.20% EMS dose with significant  shift in mean values in positive direction for almost all the traits studied.  Identification of 64 mutant lines from available population of 660 lines  confirmed highest mutagenic frequency of 43.75% by 0.15% EMS followed by  0.2% EMS (42.18%); whereas 0.10% EMS showed least mutagenic frequency. Component analysis showed medium to high GCV values for most of the traits  confirming variability of genetic nature thereby implying that clonal selection  has paramount significance in the identification of elite lines. Divergence  nalysis grouped 92% mutagenic lines in cluster 1 followed by 6.1% in cluster  2 and 1.5% in cluster 3. Maximum contribution towards divergence of most of  the traits was recorded by lines ‘SS/EMS-3/113’, ‘SS/EMS-3/132’, ‘SS/EMS 3/130’ and ‘SS/EMS-1/219’. Per se performance studies identified 18 extra ordinary lines which showed significant superiority over base population for  floral, foliar, corm and quality attributes and thus can be harnessed for  commercial exploitation for enhancement in factor productivity per unit area.
Keywords: Divergence; ethyl methane sulphonate; mutation; saffron; variability